The Community Source Approach to Software Development and the Kuali Experience. - MANLU LIU; HANSEN, SEAN; QIANG TU (Communications of the ACM, 2014)
The article focuses on the use of the community source methodology in computer software development. It states that community source provides a cost-effective sustainable method for higher education institutions to manage enterprise information and is an innovative approach to enterprise application development. It mentions that community source allows multiple institutions to pool resources toward a common goal and shares value creation to ensure innovative potential and flexibility. It talks about the comprehensive administrative software suite Kuali which targets the needs of higher education institutions and began as a partnership between the National Association of College and University Business Officers and Indiana University. INSET: Colorado State University Early Experience with Kuali.